Pengembangan e-modul pembelajaran Sejarah berbasis multikultural tingkat SMA - Slamet Sujud Purnawan Jati; Iqbal Maulana Razaq; Aniek Handajani; Wahyu Djoko Sulistyo (Jurnal Praksis dan Dedikasi Sosial, 2026)
Developing multicultural-based e-modules for History learning of senior high school level History education has an important role in instilling national awareness and tolerance among the nation's youth. However, there are still many problems related to history learning at high school level, such as students feel bored, history teachers lack of historical insight, monotonous learning, history books merely discuss historical facts and emphasizing less on multiculturalism. In addition, there is a new policy on in-depth learning that many history teachers have not understood, particularly history teachers in Malang. Hence, it is crucial to provide insight to history teachers by holding a workshop on developing multicultural-based e-modules for history learning fitted with the In-Depth Learning curriculum. This community service aims to develop multicultural-based e-modules for history learning that are used by high school teachers and students. Also, it is conducted to provide teaching materials that foster tolerance, respect for diversity and strengthen nationalism in Indonesia’s multicultural context. This research is carried out using a qualitative method with participatory action research. The target of the workshop activity is the history teachers in Malang. The results of the community service show that after the workshop, teachers can develop multicultural-based history e-modules. Moreover, the developed e-modules increase student learning motivation, broaden historical insights with a multicultural perspective, and facilitate teachers in presenting materials interactively. Dissemination of the workshop results are carried out through journal articles, social media, and posters. Furthermore, the multicultural-based history e-modules will be implemented in several high schools to enhance students' understanding of national identity and sense of Indonesian nationalism. Pendidikan sejarah mempunyai peranan penting dalam menanamkan kesadaran kebangsaan dan toleransi diantara generasi bangsa. Namun masih banyak permasalahan terkait pembelajaran sejarah di tingkat SMA, seperti siswa merasa bosan, guru sejarah kurang wawasan kesejarahan, pembelajaran monoton, buku sejarah hanya membahas fakta sejarah dan kurang menekankan multikulturalisme. Apalagi ada kebijakan baru tentang pembelajaran mendalam yang belum dipahami sebagian besar guru sejarah, khususnya guru MGMP sejarah di Malang. Oleh karenanya penting untuk memberikan wawasan kepada guru sejarah dengan mengadakan workshop pengembangan e-modul pembelajaran sejarah berbasis multikultural yang sesuai dengan kurikulum pembelajaran mendalam. Kegiatan ini bertujuan untuk mengembangkan e-modul pembelajaran sejarah berbasis multikultural yang digunakan oleh guru dan siswa tingkat SMA. Selain itu kegiatan ini untuk memenuhi kebutuhan bahan ajar yang mampu menumbuhkan sikap toleransi, menghargai keberagaman, serta memperkuat rasa nasionalisme dalam konteks multikultural Indonesia. Kegiatan ini dilakukan memakai metode kualitatif dengan participatory action research. Sasaran kegiatan workshop adalah guru MGMP Sejarah di Malang raya. Hasil kegiatan menunjukkan bahwa setelah workshop guru mampu menyusun e-modul sejarah berbasis multikultural. Selain itu e-modul yang dikembangkan mampu meningkatkan motivasi belajar siswa, memperluas wawasan sejarah dengan perspekstif multikultural, serta memudahkan guru dalam menyajikan materi secara interaktif. Diseminasi hasil workshop dilakukan melalui artikel jurnal, media sosial dan poster. Selanjutnya e-modul sejarah berbasis multikultural akan diimplementasikan di beberapa sekolah tingkat SMA/sederajat sehingga dapat meningkatkan pemahaman identitas nasional dan rasa nasionalisme Indonesia di kalangan peserta didik.